2015
DOI: 10.3390/biology4040881
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Bony Fish Macrophages

Abstract: Macrophages are found across all vertebrate species, reside in virtually all animal tissues, and play critical roles in host protection and homeostasis. Various mechanisms determine and regulate the highly plastic functional phenotypes of macrophages, including antimicrobial host defenses (pro-inflammatory, M1-type), and resolution and repair functions (anti-inflammatory/regulatory, M2-type). The study of inflammatory macrophages in immune defense of teleosts has garnered much attention, and antimicrobial mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 202 publications
(252 reference statements)
1
67
0
1
Order By: Relevance
“…In bony fish, the best characterized macrophage phenotype is reminiscent of the mammalian pro-inflammatory M1 state [reviewed in (Hodgkinson et al 2015)]. Studies have demonstrated that following exposure to various activation stimuli, bony fish macrophages display increased phagocytosis, increased production of reactive oxygen intermediates, elevated expression of inducible nitric oxide synthase (iNOS/NOS2), phagolysosomal acidification, and nutrient deprivation (Grayfer et al 2014c; Neumann et al 2000; Rieger et al 2010).…”
Section: 3 Evolutionary Conservation Of M1/m2-like Functional Hetermentioning
confidence: 99%
See 1 more Smart Citation
“…In bony fish, the best characterized macrophage phenotype is reminiscent of the mammalian pro-inflammatory M1 state [reviewed in (Hodgkinson et al 2015)]. Studies have demonstrated that following exposure to various activation stimuli, bony fish macrophages display increased phagocytosis, increased production of reactive oxygen intermediates, elevated expression of inducible nitric oxide synthase (iNOS/NOS2), phagolysosomal acidification, and nutrient deprivation (Grayfer et al 2014c; Neumann et al 2000; Rieger et al 2010).…”
Section: 3 Evolutionary Conservation Of M1/m2-like Functional Hetermentioning
confidence: 99%
“…Notably, CSF-l-derived human monocytes are more susceptible to infection with an attenuated strain of Mycobacterium bovis (Bacille de Calmette et Guérin), the causative agent of tuberculosis in cattle, as determined by increased phagocytosis and enhanced bacterial outgrowth (Verreck et al 2004, 2006). Although the modulating potential and putative suppressive role of CSF-1 in macrophage polarization is partially recapitulated in mice (Fleetwood et al 2007) and to some extent in Xenopus , in bony fish CSF-1 stimulation appears to skew macrophages towards an M1-like state (Grayfer et al 2009) and reviewed in (Hodgkinson et al 2015). …”
Section: 3 Evolutionary Conservation Of M1/m2-like Functional Hetermentioning
confidence: 99%
“…It should be emphasized that these M1/M2 functional subsets represent opposite boundaries of a continuum of possible functional states. Notably, the mammalian CSF-1 contributes to the this functional heterogeneity of macrophage-lineage cells by polarizing macrophages towards the M2 phenotype (Hamilton et al, 2014), whereas the teleost fish CSF-1 appears to skew macrophages towards an M1-like state [reviewed in (Hodgkinson et al, 2015)]. Intriguingly, the interleukin-34 (IL-34) cytokine, which bears no sequence identity with CSF-1, also binds to, and activates with CSF-1R in mammals, thereby contributing to monopoiesis (Chihara et al, 2010; Liu et al, 2014; Ma et al, 2012; Droin and Solary, 2010; Lin et al, 2008; Wei et al, 2010).…”
Section: Monopoiesis In Anuramentioning
confidence: 99%
“…Decreased antigen presentation and an overall suppressive response have also been associated with the M2 macrophage response (Mosser, 2003), and certain cytokines characteristic of M2 response can also downregulate MHCII expression and antigen presentation (de Waal Malefyt et al, 1991). M2 macrophages can be further divided into several phenotypes based on gene expression profiles in mammals, and these phenotypes seem to be present in fish (Hodgkinson et al, 2015). The macrophage states can be induced by several cytokines, such as IL4 or IL13, or the macrophages themselves can produce certain cytokines such as IL10.…”
Section: Regulation Of the Inflammatory Responsementioning
confidence: 99%